SCA-1/Ly6A Mesodermal Skeletal Progenitor Subpopulations Reveal Differential Commitment of Early Limb Bud Cells - Marín-Llera, Jessica Cristina; Lorda-Diez, Carlos Ignacio; Hurle, Juan Mario; Chimal-Monroy, Jesús (Frontiers in Cell and Developmental Biology, 2021)
At early developmental stages, limb bud mesodermal undifferentiated cells are morphologically indistinguishable. Although the identification of several mesodermal skeletal progenitor cell populations has been recognized, here we identified and characterized the differentiation hierarchy of two new early limb bud subpopulations of skeletal progenitors defined by the differential expression of the SCA-1 marker. Based on tissue localization of the Mesenchymal Stromal Cell-associated markers (MSC-am) CD29, Sca-1, CD44, CD105, CD90, and CD73, we identified, by multiparametric analysis, the presence of cell subpopulations in the limb bud capable of responding to inductive signals differentially namely, sSca+ and sSca- cells. In concordance with its gene expression profile, cell cultures of the sSca+ subpopulation showed higher osteogenic but lower chondrogenic capacity than those of sSca-. Interestingly, under high-density conditions, fibroblast-like cells in the sSca+ subpopulation were abundant. Gain-of-function employing micromass cultures and the recombinant limb assay showed that SCA-1 expression promoted tenogenic differentiation, whereas chondrogenesis is delayed. This model represents a system to determine cell differentiation and morphogenesis of different cell subpopulations in similar conditions like in vivo. Our results suggest that the limb bud is composed of a heterogeneous population of progenitors that respond differently to local differentiation inductive signals in the early stages of development, where SCA-1 expression may play a permissive role during cell fate.